2010
DOI: 10.1245/s10434-010-0914-6
|View full text |Cite
|
Sign up to set email alerts
|

New Metastatic Lymph Node Ratio System Reduces Stage Migration in Patients Undergoing D1 Lymphadenectomy for Gastric Adenocarcinoma

Abstract: Background The AJCC/UICC staging system for gastric cancer incorporates the absolute number of metastatic lymph nodes (N status) and is optimally used when ≥15 nodes are examined. The ratio of metastatic to examined nodes (N ratio) is an effective prognostic tool, but has not been examined in Western patients undergoing primarily D1 lymphadenectomy. Methods 257 patients with gastric adenocarcinoma who underwent gastric resection between 1995 and 2005 at our institution were examined. Novel N ratio intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 42 publications
(44 reference statements)
3
46
1
Order By: Relevance
“…Lymph node ratio has already been reported as a prognostic factor in various series of advanced gastric cancer [12][13][14][15][16][17][18], but the prognostic relevance was observed again in this study with the Japanese population treated by the current standard of care.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Lymph node ratio has already been reported as a prognostic factor in various series of advanced gastric cancer [12][13][14][15][16][17][18], but the prognostic relevance was observed again in this study with the Japanese population treated by the current standard of care.…”
Section: Discussionmentioning
confidence: 47%
“…Lymphatic permeation (ly) and vascular permeation (v) are defined as ly0, ly 1, ly 2, and ly 3 and v0, v1, v2, and v3 by infiltrative grade, but we classified ly and v as absence or presence. Percentage of metastatic lymph nodes, as lymph node ratio greater than or equal to a certain value designated by the researchers, has been defined as one of the most promising prognostic predictors by our previous studies [12][13][14] and elsewhere [15][16][17][18]. Histologically, there are two major types of gastric adenocarcinoma (Lauren's classification).…”
Section: Clinicopathological Factorsmentioning
confidence: 99%
“…To evaluate the rN staging system, some previous reports excluded patients with fewer than 16 LNs retrieved [16,20,22]; some researchers preferred the patients treated by limited lymphadenectomy, [9,10,18,23]; and some centers evaluated the rN system as an independent prognostic factor in gastric cancer regardless of the type of lymphadenectomy, or in both [15 and B15 LNs examined [17,19,24,25], as we did in our report. All the reports indicated that the rN staging system has superiority in prognosis assessment compared with the traditional AJCC pN system.…”
Section: Discussionmentioning
confidence: 88%
“…The Cox multivariate analysis showed that rN has a prognostic value independent of the extent of lymphadenectomy. Many previous reports used Cox multivariate examinations, including both pN stage and rN stage, for proving the superiority of the LN ratio system [9,[15][16][17][18][19][20]. The pN and rN systems, two definitions of classifications for staging lymph node status, were highly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation